Species distribution modeling and geological patterns Of tribe schismatoglottideae (araceae) in sundaland - Tung, Lay Soon (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Sundaland is a biogeographical region of Southeast Asia which encompasses the Malay Peninsula and the islands on the Sunda shelf, including Borneo, Java, Sumatra and their surrounding islands. Tribe Schismatoglottideae (Araceae) is a terrestrial, rheophytic or lithophytic herbs widespread in humid tropical Asia and with some genera are overwhelmingly endemic to Borneo where out of more than 250 species, 95% are endemic within Borneo. However, many areas in Sundaland still remain very poorly known especially Kalimantan cover the largest land area within Borneo. Therefore, this study provided preliminary information of potential habitat suitability based on existing species distribution in the region using the MaxEnt species distribution modeling method. The species dataset used in this study comprises 601 records of species distribution in eight genera of tribe Schismatoglottideae. Further databases used in this study were obtained from ISRIC World Soil Information database and WorldClim database as environmental variables. The genus distribution models for eight genera were generated; bioclimate and soil parameters affecting the distribution were discussed. The second part of the study provides the investigation on the genus distribution in Sabah and Sarawak (Malaysian Borneo) against the framework of historical geological formations. A total of 947 species iv records were plotted onto the digital map. The maps were produced by combining the topographic map (base map) together with geological map for Sabah and Sarawak provided by Orr & Associates organization. The combined digital map was re-projected to Universal Transverse Mercator (UTM) coordinate system using ArcGIS 9.3. Out of 64 geological formations in Sarawak, tribe Schismatoglottideae occurs in 23 formations where in Sabah, out of 58 geological formations in Sabah, tribe Schismatoglottideae occurs in 13 formations.